Liquid desiccant membrane regeneration of des for air conditioning systems using electrodialysis technique - Oladosu, T.L. (Springer Science and Business Media Deutschland GmbH, 2020)
The quest for energy-saving dehumidification approach paved the way to liquid desiccant air conditioning system (LDAC). Non-corrosive and hygroscopic ionic liquids are compelling as potential liquid desiccants. However, toxicity, biocompatibility, biodegradability, and viscosity of ionic liquids still pose concerns. Binary deep eutectic solvent (DES) of choline chloride and ethylene glycol is proposed as potential greener liquid desiccant in air conditioning systems, by considering desiccant regeneration performance via electrodialysis technique. A parametric study of the liquid desiccant regeneration was investigated numerically using COMSOL Multiphysics commercial software. The results showed the influence of the operational parameters on the overall performance prediction. Electrodialytic regenerated desiccant in a single-cell analysis optimally yielded about 74Â mol/m3 of aliphatic choline species at 313.15Â K working temperature and 1.25Â V DC power input. 3.59Eâ02Â g/m2s DES flux was obtained in the regenerated channel at 2Â V power input. The results aid in predicting DES desiccant regeneration capacity, understanding electrodialysis phenomenon, and performance influential parameter interactions. Â© Springer Nature Singapore Pte Ltd 2020.